Mathematical Connection Ability : Impact of Contextual Teaching And Learning Approaches in Flat Side Space Lesson - kandari, kurnia; Zanthy, Luvy Sylviana (Desimal: Jurnal Matematika, 2020)
The purpose of this research is to analyze the students' mathematical connection ability before and after getting Contextual Teaching and Learning. The subjects were the 26 students of class VIII-A at SMI 1 MANIIS, Purwakarta Regency. The research used the descriptive method with the qualitative approach. The data for the analysis were from the test to student consist of 5 questions with 4 different indicators. The results shows that all students have moderate in mathematical connection ability with the overall results of 65.83%. For the results of each indicator, there is one indicator that has not been met, understanding the equivalent representation from one procedure to another one, or from one concept to another concept. So it can be concluded that the mathematical connection ability in terms of the Contextual Teaching and Learning approach has a significant effect.